Impact of weirs in altering benthic macroinvertebrate assemblages and composition structure in the Luvuvhu River Catchment, South Africa - Munzhelele, Humbulani E.; Barnhoorn, Irene E. J.; Addo-Bediako, Abraham; Ramulifho, Pfananani A.; Luus-Powell, Wilmien J. (Frontiers in Environmental Science, 2024)
Stream flow weirs disrupt river flow regimes, physical conditions, and biological composition of rivers, posing significant threat to the river’s functionality, integrity, and sustainability. Home to diverse aquatic organisms, there is a lack of impact assessment of weirs on the stream of the Luvuvhu River Catchment (LRC). The aim of this study was to examine the impact of six weirs on aquatic macroinvertebrate assemblages and composition across five streams. A total of six sampling surveys on macroinvertebrates and physico-chemical parameters were conducted upstream and downstream of six weirs in 12 months between June 2021 and June 2022. The South African Scoring System score (SASS score) and Average Score per Taxon (ASPT) indices were used to compare organisms’ response between upstream and downstream of weirs. Generalized linear mixed models (GLMM) were used to determine the effect of physico-chemical variables on macroinvertebrate assemblage, while the CCA was employed to assess similarities between downstream and upstream sampling points across various sites. A total of 18,914 macroinvertebrate individuals were observed from 65 families during the survey. In upstream sections, the SASS score was driven by habitat integrity, electrical conductivity, and water depth, while ASPT responded significantly to habitat integrity, pH, dissolved oxygen and electrical conductivity. In the downstream sections, the SASS score increased with an increasing habitat integrity score and river width, while decreasing with elevation and pH levels. ASPT increased with increasing habitat integrity and elevation in the downstream sections, while decreasing with increasing river width and water temperature. This study’s findings suggest habitat integrity is largely driving aquatic abundance and assemblage in the LRC, and it is therefore important to maintain the ecological integrity of rivers.